Investigating the Effect of the Rock-Socketed Depth of the Hinged Cable-Anchored Pile on the Earthquake Response Characteristics of Supporting Structures - A. Fa-you; Ming-chang Hei; Shi-qua Yan; Peng Zhang (Advances in Civil Engineering)
In order to meet the design requirements of the anti-slide pile, the form of the anchor-pull pile is often adopted in engineering applications. In the present study, the seismic response characteristics of hinged cable-anchored piles with different rock-socketed depths are analyzed using a large-scale seismic model test platform and numerical simulations. The obtained results show that the rock-socketed depth significantly affects the seismic response of the pile-anchor system. It is found that, as the rock-socketed depth increases under the same seismic conditions, the peak acceleration at the top of the anchored pile, the peak dynamic Earth pressure behind the pile, the axial force of the anchor rod, and the bending moment of the pile body decrease and the seismic stability of the anti-slide pile improves. It is concluded that, in the seismic design of anchor-pulled piles, increasing the rock-socketed depth of the anchor is an appropriate scheme to improve the seismic performance of anchor-pulled piles. The research results have a certain significance for improving the understanding of the seismic response law of hinged cable-anchored piles and improving the seismic design.